Philosophical Posthumanism: An Ontological Assessment by Contemporary Muslim Scholars - Long, Ahmad Sunawari; Jubba, Hasse; Ismail, Mohd Hatib; Ab Rahman, Zaizul (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This article examines the ontological foundations of philosophical posthumanism and critically examines its central claims through the lens of contemporary Muslim thought. Rooted in postmodern critiques of Enlightenment humanism, posthumanism challenges conventional ideas of human identity, agency, and moral status by emphasizing hybridity, technological mediation, and the interconnectedness of all forms of life—including animals, machines, and ecosystems. Through conceptual analysis and comparative hermeneutics, the study contrasts these claims with key Islamic metaphysical concepts such as fitrah (innate nature), ruh (soul), and khalifah (vicegerency). Prominent Muslim thinkers, including Seyyed Hossein Nasr, Taha Abdurrahman, Osman Bakar, and Fazlur Rahman, argue that posthumanist ontology undermines the sacred status of the human being, potentially leading to spiritual alienation by denying transcendence and moral responsibility. While acknowledging the ethical and ecological contributions of posthumanism, the paper contends that its core assumptions remain incompatible with the Islamic worldview, which affirms human dignity, metaphysical purpose, and divinely ordained responsibility within the cosmos.